THE EFFECT OF BABY MASSAGE ON THE QUALITY OF SLEEP IN BABIES IN THE PRACTICE OF MIDWIVES JUWITA MEDAN CITY YEAR 2024 - Suci Ramadayati; Herna Rinayani Manurung; Astaria Br Ginting; Febby Aisyah Putri; Sodiria Zega; Selli Kurnia Wulantari Tarigan; Jesyca Syahrani, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
The neonatal mortality rate in Indonesia shows a worrying dynamic, where Maternal Perinatal Death Notification (MPDN) data recorded a surge in infant mortality from 20,882 cases in 2022 to 29,945 cases in 2023. At Juwita's Midwife Practice, Medan Marelan District, Medan City, the practice of baby massage is still little carried out by the community as an effort to improve the quality of sleep of babies in 2016 reaching 143 toddlers. This study was conducted to assess the effect of infant massage on sleep quality in neonates using a pre-experimental design with a single group measured before and after the intervention at the Juwita Midwife Practice, Medan Marelan District, Medan City in 2024. This study falls under the category of experimental research, where the research design is used to identify cause-and-effect relationships through independent variables by the researcher. All babies born at the Juwita Midwife Practice, Medan Marelan District, Medan City were samples in the study. Data shows that during May to June there were 20 pregnant women who gave birth. Based on the results of the calculation, the p value is 0.001<a(0.005). These findings indicate that the alternative hypothesis (Ha) is proven, so it can be concluded that baby massage affects the sleep quality of babies at Juwita Midwife Practice, Medan Marelan District, Medan City. Therefore, healthcare workers are encouraged to regularly integrate baby massage services as an effort to improve babies' sleep quality.